Deutsche Mark Diplomacy : Positive Economic Sanctions in German-Russian Relations - Newnham, Randall Everest, 1966- (Book collections on Project MUSE., 2002)
Whether economic sanctions work at all, and how they work if they do, are questions that have long been debated by scholars of international relations. Using a new analytic approach, which distinguishes between positive and negative sanctions and between specific and general sanctions, this book aims both to demonstrate the importance of economic linkage and to explain the variety of forms it can take. Deutsche Mark Diplomacy draws support for its theoretical arguments from a careful study of Germany's efforts to gain political leverage over Russia via economic means from 1870 into the 1990s. Focusing on two major powers over a long period, during which regimes changed and issues varied, Randall Newnham finds strong evidence to show that positive forms of linkage such as foreign aid and trade or credit incentives are more effective than negative types such as embargoes. His book significantly expands our understanding of the role played by economic sanctions in international politics at the same time that it offers a more systematic way of explaining German foreign policy.